Socio-Cultural Impact Of Urbanization On Rural Students' Academic Performance: Empirical Evidence From Quaid-I-Azam University, Islamabad, Pakistan - Asif Nawaz , Dr. Sadia Saeed , Abid Rasool , Shahid khan , Haji Ur Rahman , Mauz Khan (Migration Letters, 2024)
The transition from rural to urban environments can significantly impact students' academic trajectories. This study delves into the sociocultural factors influencing the academic performance of rural students in an urban university setting. By examining the interplay of various social identities through an intersectional lens, this research seeks to understand the challenges and opportunities faced by these students. Furthermore, the research emphasizes how urbanization affects rural students’ academic performance and well-being, focuses on sociocultural experiences, educational opportunities, and the processes of adaptation. The Study investigates how different social identities interact to influence students' experiences in urban environments, by using Kimberlé Crenshaw's theory of intersectionality. With a sample size of 383 students, the study was conducted at Quaid-i-Azam University Islamabad, adopted a stratified random sampling design. The researcher manuall[1]y distributed an in-depth survey for data collection, and IBM SPSS Statistics version 22 was used for analysis. Results show that there is a significant trade-off among rural and urban locales, metropolitan regions providing benefits for learning and access to a wide range of services, despite possible social and economic costs. The study highlights the challenges that rural students encounter when adjusting to urban life, such as troubles with preserving cultural identity, understanding social norms, managing stress, and handling expenditures. Overall, the study underlines how essential it is for educators and decision-makers to provide inclusive educational settings that accommodate the various requirements of students moving from rural to urban settings.